2010
DOI: 10.1590/s1807-59322010001100014
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Viral Identification and Coinfections in Infants with Acute Bronchiolitis

Abstract: OBJECTIVES:To determine the viruses and risk factors associated with hospital and intensive care unit (ICU) admissions in infants with acute bronchiolitis.INTRODUCTION:Bronchiolitis is a major cause of morbidity in infants. Widespread use of molecular-based methods has yielded new insights about its etiology, but the impact of viral etiologies on early outcomes is still unclear.METHODS:Seventy-seven infants with bronchiolitis who were under two years of age and visited an emergency unit were included. Using mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
70
8
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 31 publications
18
70
8
8
Order By: Relevance
“…There were ten coinfections in our study and RSV was also the most common in coinfection. Studies showed different results about prognosis of coinfections, some of them reported that coinfections are associated with worse prognosis, however some of them found no significant difference between coinfections and infections with single virus [25,26]. In our study, there was no significant difference of prognosis between coinfections with RSV and single virus infections.…”
Section: Discussioncontrasting
confidence: 65%
“…There were ten coinfections in our study and RSV was also the most common in coinfection. Studies showed different results about prognosis of coinfections, some of them reported that coinfections are associated with worse prognosis, however some of them found no significant difference between coinfections and infections with single virus [25,26]. In our study, there was no significant difference of prognosis between coinfections with RSV and single virus infections.…”
Section: Discussioncontrasting
confidence: 65%
“…However, controversy exists regarding whether these viruses increase the severity of illness and LOS [2]. It has been reported that, while co-infections do not affect LOS or mortality, influenza virus (INF) infection is associated with increased LOS and mortality [3,4].…”
Section: Increased Severity Of Viral Infections Has Recently Been Repmentioning
confidence: 99%
“…It has been reported that, while co-infections do not affect LOS or mortality, influenza virus (INF) infection is associated with increased LOS and mortality [3,4]. Nonetheless, the impact of co-infections is, in general, still unclear [2,[5][6][7].…”
Section: Increased Severity Of Viral Infections Has Recently Been Repmentioning
confidence: 99%
“…For bronchiolitis patients in the ED, Al-Shehri et al [44][45][46][47][48] identified several predictors of hospital admission: prematurity, chronic lung disease (primarily bronchopulmonary dysplasia), atopic dermatitis, pure formula feeding (no breast feeding), passive smoking, age ≤ one year, nasopharyngeal lactate dehydrogenase value, low dew point, enterovirus infection, absence of familial atopy, rhinovirus, and co-infection. Voets et al [35] identified three predictors of hospital and ICU admission: age < six months, respiratory rate > 45 breaths per minute, and oxygen saturation < 95% at sea level.…”
Section: Predicting Hospital Admission From the Edmentioning
confidence: 99%